Microglial transcriptome diversity: The new milestone to reveal the neuroinflammation in subarachnoid haemorrhage - Junfan Chen; George Kwok Chu Wong (Wiley, 2022)
Abstract The diversity of microglial transcriptome after subarachnoid haemorrhage (SAH) was analysed for the first time. By using single‐cell RNA sequencing (scRNA‐seq), microglia were found with diverse microglial substates and significant subgroups were defined. Microglia subsets were found to interact with each other and crosstalk with other kinds of brain cells, which ultimately affected the neuroinflammation in SAH. Microglia‐mediated neuroinflammation has been considered to be the key factor in the evolution of brain injury after SAH, but the pathophysiological mechanisms are still unclear. Under these circumstances, the study comprehensively analysed the changes of microglial transcriptome after SAH, and explored possible modes of activating the inflammatory pathways. This study expanded and systemically laid out the understanding of microglia‐mediated neuroinflammation after SAH and provided strong theoretical support for future microglia modulation research in SAH.